Adapting the Digital Servuction Model to Central Banks: Case Study: European Central Bank - Silvana Prodan; Dan-Cristian Dabija (Administrative Sciences, 2023)
Central bank communication has changed over the years, following the trend of digitalization. It has been used as a tool for the implementation of monetary policies since the 1990s, when central banks started publishing their inflation reports, outlooks, and meeting minutes on the road towards greater transparency, and to help meet their price stability mandate. This mandate cannot be achieved through traditional financial instruments alone, so digital communication and marketing has become an economic policy tool. The effectiveness of the European Central Bank’s online communication tools will be tested via a GAP model, by applying an adapted version of the servuction scale to the Bank and disseminating it to 500 citizens, with the purpose of measuring citizen satisfaction with its website and communications. The servuction model focuses on high quality services that are perceived as such by private sector customers, having a strong marketing component. The originality of the research consists in adapting it to the public sector, more specifically to central banks, and by treating citizens as customers throughout the study. The model was successfully applied to the European Central Bank, demonstrating that citizens’ expectations are highest regarding both the reliability and assurance dimensions, meaning that they want to feel confident in ECB actions, and to the understandability dimension of its online content. The largest gaps between citizens’ expectations and perceptions were identified within the efficiency, understandability, and empathy dimensions. In future, the study can be replicated and adapted to both national central banks and private banks within the European Union, assessing how citizens perceive their websites, communication, and marketing strategies, with the purpose of improving the latter two, and increasing civic engagement. The model can also be adapted to narrower topics relating to sustainable digital development, such as the expectations and perceptions of citizens with regards to central bank digital currencies.